Советско-турецкие отношения: от нейтралитета до требования (1941 г.) - Christine Melkonyan (Banber Arevelagitut'yan Instituti, 2025)
Due to its strategic geographical position, before and during the World War II Turkey became an object of rivalry between the three centers of power - Germany, UK and France, as well as the USSR. Balancing between the powers of the Axis and Allies, Turkey showed that it was not inclined to openly support any of the sides, adhering to neutrality. Turkey ledК anti-Soviet policy, receiving military and technical assistance from both sides of the conflict. Only on February 23, 1945 Turkey abandoned its position of neutrality and entered the World War II on the winning side. The article examines the main trends in the presentation and assessment of Turkey’s foreign policy in the initial period of World War II. After the death of Mustafa Kemal Atatürk, the Turkish government in the late 30s of the XX century no longer needed good relations with the Soviet Union. It began to pursue a pro-Western course. His active supporter was Minister of Foreign Affairs Sh. Saradjoğlu, who replaced T. Aras on this post. At the beginning of the war, Turkey supported Britain, France, and then openly sided with Germany. At the same time, throughout the war, both Britain and Germany, though unsuccessfully, tried to drag Turkey into the war. Turkey persistently did not go to rapprochement with their northern neighbor USSR, finding various reasons for this. Eventually, Turkey signed an agreement with Nazi Germany shortly before its attack on the USSR. Some Turkish historians call Turkey's foreign policy "defensive." Britain and the United States called it a "bad example of loyalty." And to be more precise, Turkey was trying to "raise its price" in that way, that is, to "sell its loyalty as expensive as possible." In addition, in spite of the fact that Turkey remained neutral in World War II, however in 1941 the Turkish foreign policy was obviously pro-German.